Evaluation of Village Government Performance in Implementing the Village Development Movement Program (GERDEMA) in Long Bila Village, West Malinau District, Malinau Regency - Figries Niagara; Sarwono Sarwono; Riyanto Riyanto (Wacana Journal of Social and Humanity Studies, 2019)
Villages are an important part of spearheading an autonomous and sovereign democracy. Where the village has original autonomous rights based on customary law, can determine the composition of the government, regulate and manage households, and have wealth and assets. An important part in the implementation of development in the Village is the Village Government which is a strategic part of development. Village Government is a device that runs the government with other institutions and all products that are born by Village institutions. Where the village head has an important role in coordinating the performance of all institutions in the village. However, it cannot be denied that the implementation of the Village Government until now still faces a number of problems. As well as the obstacles faced by the current village administration, namely the low performance of village institutions, village government governance and community services. This problem affects the achievement of policy objectives.